Numerical Study of Aircraft Wake Vortex Evolution under the Influence of Vertical Winds - Jianhui Yuan; Jixin Liu; Changcheng Li; Zheng Zhao (Applied Sciences, 2023)
Separating wake vortices is crucial for aircraft landing safety and essential to airport operational efficiency. Vertical wind, as a typical atmospheric condition, plays a significant role, and studying the evolution characteristics of wake vortices under this condition is of paramount importance for developing dynamic wake separation systems. In this study, we employed the SST k-ω turbulence model based on an O-Block structured grid to numerically simulate the simplified wing model. We analyzed the variations in the wake vortex structure and parameters of the Airbus A320 during the near-field phase under different vertical wind directions and speeds. The results indicate that favorable vertical winds cause a “flattening” deformation in the wake vortex. Vertical winds reduce the initial vortex strength, accelerate the rate of vortex decay, and influence the trajectory of the vortex core. Notably, under wind speeds of 1~3 m/s, the decay rate is more significant than under 4 m/s. When vertical wind speeds are substantial, it can lead to irregular motion and interactions within the vortex core, forming secondary vortices.